The impact of the COVID-19 pandemic on access to mental health services and socioeconomic inequalities in Italy - Petrelli, Alessio; Ventura, Martina; Ciampichini, Roberta; Di Napoli, Anteo; Fano, Valeria; Napoli, Christian; Pacifici, Martina; Rosini, Claudio; Silvestri, Caterina; Voller, Fabio; Zucchi, Alberto; Aragona, Massimiliano (Frontiers in Psychiatry, 2024)
ObjectiveComprehensive evidence on the impact of the Coronavirus Disease 2019 (COVID-19) pandemic on the use of mental health services is scarce. The aim of this study was to evaluate the impact of the COVID-19 pandemic on the access to mental health services in Italy and to assess the socioeconomic and citizenship inequalities for the same outcome.MethodsA population-based longitudinal open cohort of residents aged ≥ 10 years was established in three large centers covering about 6 million beneficiaries (nearly 10% of the entire population) of the Italian National Health Service (NHS) from 01 January 2018 to 31 December 2021. The primary outcome of interest was the first access to one of the following mental health care services (FAMHS): outpatient facilities, hospital discharges, psychiatric drug prescriptions, emergency room admissions, residential and day care facilities, co-pay exemptions. To evaluate the effect of the COVID-19 pandemic on FAMHS, the temporal trend of FAMHS rates was investigated through an interrupted time series (ITS) analysis of their monthly rates. Crude incidence rates per 100,000 person days with 95%CI were calculated comparing the two time periods (pre- and post-COVID-19) by sex, age group, deprivation index (as a proxy of socioeconomic status), and citizenship. Finally, adjusted rates and rates ratios with 95%CI were estimated via ITS analysis using a step-change model.ResultsITS analysis for the trend of FAMHS rates showed a significant drop at the outbreak of the pandemic in crude rates and after adjusting for age, sex, deprivation level, and citizenship (RR=0.83 p<0.001). After the outbreak of COVID-19, the trend increased, with rates returning to pre-pandemic levels. Adjusted incidence rate ratios (IRRs) showed a higher probability of having a FAMHS for females, Italians, and for residents in the most deprived areas. A gradient of higher rates with the increase in age was observed. Greater COVID-19 impact was found on the most deprived areas of residence, with a reduction in IRRs from pre- to post-COVID-19 significantly stronger.ConclusionsThe COVID-19 pandemic increased socioeconomic inequalities in mental health in Italy. Population-based cohorts are the most powerful instrument to monitor inequalities in access to mental health services and to provide timely information to drive policy.